MODERN GEODYNAMICS OF THE WESTERN ALTAI-SAYAN REGION, FROM GPS DATA - Timofeev V.Yu.; Ardyukov D.G.; Duchkov A.D.; Zapreeva E.A.; Calais E. (My University, 2003)
We report results from a GPS network installed following special criteria in the framework of an international project and implications for recent crustal movements in the western Altai-Sayan region. The network includes one permanent (NVSK, near Novosibirsk) and 17 campaign sites resurveyed yearly in the Altai mountains and their northern surroundings. The sites were operated with three Trimble 4700 GPS receivers and hard-mounted antennas at geodetic marks, in 2-3 day sessions at each site. The experience of seasonal and permanent monitoring along the ∼ 76 km Talaya-Irkutsk baseline was used to analyze some methodological issues of GPS measurements.
Keywords: Permanent and campaign GPS measurements; crustal strain; Gorny Altai; Altai-Sayan region